Centralized Local Development versus Localized Central Arrangement in Village Autonomy Policy Implementation in Indonesia - Hariyati, Desy; Holidin, Defny; Mulia, Imas Cempaka (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
Amidst fluctuate central-local governmental relations, extended decentralization policy to village level prompt discourses as to whether the policy could exploit local wisdom within which villages are supposedly develop. This article aims at explaining implications of centralized local development in Indonesia and which ways the village governments and communities exploit local wisdoms to implement localized central arrangement under the 2014 Village Law. A qualitative case study in two villages in two special autonomous provinces in Indonesia representing rich traditional culture-based tourism respectively is conducted. Data is gathered through semi-structured in-depth interviews with some key informants and document analyses. Following that, the article argues that reciprocal relations between local wisdom and practices of village autonomy are lacking, whereby organic and traditional values are not compatible with modern and formal bureaucratic nature of village governance. Village apparatuses has rather sought for satisfying local development accountability than incorporating existing local wisdom therein. While the 2014 Village Law requires each village to integrate local wisdom living naturally in villages, its standardized procedures render them to shift their accountability from supposedly held to local people to municipal governments. This makes centralization of local development happened by and within local governments under localized administrative arrangements imposed by the central government.